(untitled) (Conference on English Language Teaching, 2023)
Motivation is an important aspect of the student in learning process at school. The purpose of this study was to analyze the instrumental and integrative motivation of eighth grade students at SMPN 3 Tarakan. This research used a mixed method, namely mix-method, determining the sample is done by random sampling technique. The study took 31 respondents from class VIII-1. Researchers used triangulation methods to check the validity of data such as checking documentation, observation, questionnaires, and interviews. The results of this study show 1) the dominating factor of mixed learning is instrumental motivation. 2) the factor that influences instrumental and integrative motivation of blended learning is that students like learning English because they want to get a complete score on the KKM in English learning and their report card scores. Other results show learning English helps them to improve their English skills and be more knowledgeable. 3) The relationship between instrumental and integrative motivation in English learning achievement. Which the results show that; first, instrumental motivation (X1) with integrative motivation (X2) is correlated, it can be shown sig. (2-tailed) 0.000 <0.05. Second, instrumental motivation (X1) with English learning achievement (Y) does not correlate, this is indicated by the sig. (2-tailed) 0.359 > 0.05. Third, integrative motivation (X2) with English learning achievement (Y) does not correlate can be seen in sig. (2-tailed) 0.369 > 0.05. Thus, based on the above results, it can be concluded that there is no relationship between instrumental motivation and integrative motivation to student learning achievement. In other words, students with high motivation cannot be concluded that their English grades or their achievement in learning English must be good and vice versa.